Cremophor EL Alters the Plasma Protein Binding and Pharmacokinetic Profile of Valspodar in Rats - Binkhathlan, Ziyad (Drug Research, 2017)
Cremophor EL is a nonionic surfactant widely used in pharmaceutical formulations. Nonetheless, there are several reports on the influence of this excipient on the protein binding, pharmacokinetics, and pharmacodynamics of drugs. Valspodar is an investigational non-immunosuppressive derivative of cyclosporine A, used in clinical trials for treatment of multidrug resistant tumors. The formulation of valspodar (Amdray®) contains cremophor EL and ethanol as solubilizing agents. The main aim of the current study was to assess the plasma protein binding (in vitro) and the pharmacokinetic profile of valspodar in the cremophor EL-based formulation in comparison to a cremophor EL-free formulation following intravenous (i. v.) administration to rats. Valspodar dissolved in PEG 400/ethanol (diluted in Dextrose 5%) was used as the cremophor EL-free formulation. The in vitro plasma unbound fraction (f u) of valspodar in the cremophor EL formulation was 2.3-fold higher than the PEG 400/ethanol formulation. Following a single i. v. dose of 5 mg/kg, valspodar in the cremophor EL-based formulation had around 50% lower plasma AUC compared to the PEG 400/ethanol formulation. Moreover, the cremophor EL formulation had significantly higher volume of distribution and clearance in comparison to the PEG 400-based formulation. The results highlight the significance of excipient-drug interaction that should not be overlooked during the early stages of drug development.
Keywords: drug delivery; p-glycoprotein; pharmacokinetics